Assistance needed for the integration of orphaned and vulnerable children - views of South African family and community members - Melvyn Freeman; Nkululeko Nkomo (Taylor & Francis Group, 2006)
Guardianship within families is often regarded as the most viable and preferred option for orphaned and vulnerable children (OVC). However, this will place a considerably increased burden on the new caregivers of these children. This study examines whether assistance to prospective families would incline them towards incorporating children and, if so, what would act as 'threshold' incentives for them. Adults (N = 1 400) in diverse locations and of various 'relational proximity' to children were interviewed in three high HIV/AIDS prevalence provinces in South Africa. Close relatives were more inclined to take in children and would generally require lower levels of assistance than more distanced adults. Nonetheless, for most poor families, no matter their relation to the child, help is critical. More distanced families, friends and strangers also showed a strong willingness to incorporate children - provided they receive sufficient help. For all categories, the greater the assistance the more likely they would be to take in children.While direct financial assistance was important, assistance with education-related costs and having a trained and caring person come in 'now and then' to help were also significant factors. The age and HIV status of the child were viewed as important intervening factors in deciding whether or not to take in an additional child/ren by some people.